The Role of Women in the Economic Contribution to the Household Economy: Employment Analysis Paid and Unpaid - Smith Sell Minot; Omvedt Morini Russell; Dush Creswell; Pesando Eagly; Ferrant Marson (Intitute of Computer Science (IOCS), 2022)
This research offers a comprehensive examination of women's economic contributions to the household economy, encompassing both paid employment and unpaid labor. Through a multifaceted analysis, the study delves into the intricate landscape of women's roles, challenges, and the transformative potential of initiatives aimed at fostering gender equality. The findings reveal the expanding participation of women in various sectors of paid employment, highlighting its positive impact on economic empowerment, household income, and overall economic growth. Equally significant is the unveiling of women's unpaid labor—caregiving, emotional support, and household chores—often rendered invisible within traditional economic frameworks. The research underscores the urgency of recognizing and valuing these contributions to rectify historical oversight and more accurately depict women's impact on households and economies. However, persistent gender inequities, unequal distribution of household responsibilities, and resistance to change present challenges that require targeted policy interventions and cultural shifts. Through collective action, encompassing policy changes, cultural transformations, and inclusive attitudes, societies can leverage the diverse economic roles of women to pave the way for a more equitable and prosperous future